Circulating angiopoietin-like protein 8 (ANGPTL8) and steatotic liver disease related to metabolic dysfunction: an updated systematic review and meta-analysis - Abdelhameed, Farah; Lagojda, Lukasz; Kite, Chris; Dallaway, Alexander; Mustafa, Attia; Than, Nwe Ni; Kassi, Eva; Randeva, Harpal S.; Kyrou, Ioannis (Frontiers in Endocrinology, 2025)
BackgroundSteatotic liver disease related to metabolic dysfunction is the most common cause of chronic liver disease globally. The spectrum of this condition includes steatosis and steatohepatitis and was previously referred to as non-alcoholic fatty liver disease (NAFLD) but has been renamed as metabolic dysfunction-associated fatty liver disease (MAFLD) and more recently as metabolic dysfunction-associated steatotic liver disease (MASLD). Angiopoietin-like protein 8 (ANGPTL8), also known as betatrophin or lipasin, regulates triglycerides and has emerged as a potential novel biomarker for steatosis/steatohepatitis. Therefore, this systematic review aimed to identify and synthesize the evidence on the possible association of circulating ANGPTL8 concentrations with NAFLD, MAFLD or MASLD.MethodsPubMed/MEDLINE, Cochrane Library, EMBASE, and Web of Science were searched for studies published in English reporting circulating ANGPTL8 concentrations in adults with NAFLD or MAFLD or MASLD and controls. A meta-analysis was performed, reporting the standardized mean difference (SMD) of circulating ANGPTL8 concentrations between these two groups. Study quality and risk of bias were assessed using the NIH quality assessment tool and RoBANS 2, respectively.ResultsOf the 104 identified publications, eight studies were eligible for this systematic review, whilst seven were also eligible for meta-analysis (543 NAFLD or MAFLD cases vs. 352 controls). Circulating ANGPTL8 concentrations were significantly higher in patients with NAFLD or MAFLD compared with controls (SMD: 0.62, 95%CI: 0.28-0.97; p<0.001). Considerable heterogeneity was noted among these studies, with six studies having high risk of bias in at least one RoBANS 2 domain.ConclusionThese findings present up-to-date comprehensive evidence indicating that adults with steatotic liver disease related to metabolic dysfunction exhibit higher circulating ANGPTL8 concentrations compared with controls. Given the need for novel screening/diagnostic biomarkers for steatosis/steatohepatitis, as well for additional drug targets, large and prospective studies are required to confirm this association and explore its temporal direction, particularly under the new MASLD diagnosis/term.